Antropologia ed esperienza religiosa - Ales Bello, Angela (B@belonline, 2021)
The paper contains my comment of Massimo De Angelis book’s on Nietzsche, in particular regarding two main points: his anthropology in relationship with Husserl’s philosophical-phenomenological anthropology and the question of Übermensch. It is interesting to note that regarding the first one in both thinkers one can find a reflection on psyche and spirit, regarding the second one Nietzsche’s attempt to reach something that is ‘beyond’ the human shows his religious tension. Not being able to arrive at God he tries to divinize the human, but at last he is not satisfied with it. For this reason one must answer affirmatively to the question that one finds in the book’s title: Need we God?